HANDLING OF COAL DUST AT COAL HANDLING FACILITY IN COAL POWER PLANT USING SOFT SYSTEM METHODOLOGY (SSM) APPROACH - Akhyar Zuniawan; Iphov Kumala Sriwana (SINERGI, 2019)
Currently, many coal-fired powers plants are built to supply electrical energy needs in Indonesia due to relatively inexpensive raw materials and abundant in Indonesia. Handling of coal is mostly done at the power plant using coal handling facilities consisting of ship unloaders, conveyor belts, stock piles, silos or bunkers. The problem that arises in the coal handling facility is dust from coal that fells or hovers in the air so that it can interfere with the environment and health both for workers in the Coal Power and residents around the Coal Power. The purpose of writing this paper is to eliminate the spread of coal dust that arises due to coal handling equipment that is not precise and imperfect. The method used is the Soft System Methodology (SSM), which is a systematic approach used to analyze and solve problems in complex and messy situations. This paper examines the benefits of applying SSM to knowledge management issues in handling coal dust at a power plant. Improvement is done by upgrading coal handling equipment (ship unloader, conveyor belt, stock pile) with the addition of dust suppression, proper sealing system, dust bag, and training to operators on the impact and handling of coal dust and coal handling equipment maintenance, so resulting in a significant decrease in the spread of coal dust, creating a working environment and the environment becomes clean, healthy and safe.